JUGULAR PHLEBECTASIS AND ACHALASIA CARDIA: A case report and review literature - JIANPERAPONG, Suporn; THONGSIBKAO, Nitaya (The ASEAN Journal of Radiology, 2023)
Internal jugular vein phlebectasis and achalasia cardia were diagnosed ina 10 year -old boy. Chest film revealed posterior mediastinal mass. Ultrasonography of the neck showed fusiform dilatation of internal jugular vein and dilated esophagus. Esophagogram showed dilated esophagus with "Bird beak" or "Rat tail" appearance of distal part. The treatments of achalasia cardia were Heller’s operation and esophageal dilatation and there was no treatment for phlebectasis.